Pollen source diversity in Apis cerana beekeeping around Ir. H. Djuanda Grand Forest Park, West Java, Indonesia - CIKA ASTI AMALIA; FELICIEN AMAKPE; HANANI ROSY AZZAHRA; DEA NAVITA HASANAH; VIRANTI KARTIKA PUTRI; AUREL SATYANING ATI; ALDILA DIANI RAMADAN; SYA SYA SHANIDA; JOKO KUSMORO; WAWAN HERMAWAN; INDRI WULANDARI; TEGUH HUSODO (Society for Indonesian Biodiversity, 2025)
Abstract. Amalia CA, Amakpe F, Azzahra HR, Hasanah DN, Putri VK, Ati AS, Ramadan AD, Shanida SS, Kusmoro J, Hermawan W, Wulandari I, Husodo T. 2025. Pollen source diversity in Apis cerana beekeeping around Ir. H. Djuanda Grand Forest Park, West Java, Indonesia. Biodiversitas 26: 5405-5422. Honey bees play a crucial role in maintaining ecosystem functioning through pollination, yet their foraging ecology is strongly influenced by floral resource availability across habitats and seasons. This study investigated the pollen spectrum of Apis cerana in the Ir. H. Djuanda Grand Forest Park, West Java, Indonesia, during the rainy season. Pollen traps were installed in apiaries located at the Deer Breeding Site (interior forest) and Maribaya Site (forest edge) to collect samples for palynological analysis. A total of 32 pollen types from 20 families were identified, with higher richness in the Deer Breeding Site (25 types) than in Maribaya (21 types). Family-level analyses indicated the dominance of Asteraceae, followed by Fabaceae and Lauraceae. At the species level, Tithonia diversifolia emerged as the most dominant pollen type based on the Important Value Index (IVI), accompanied by Mimosa pudica, Sphagneticola trilobata, and Persea americana. Diversity indices showed moderate pollen diversity overall (H?: 1.76), with greater heterogeneity in the interior forest (H?: 1.87) compared to the edge habitat (H?: 1.31). These results demonstrate both the ecological importance and risks of invasive species such as T. diversifolia and S. trilobata, which provide abundant forage but may threaten native flora. Conversely, native species such as Schima wallichii and Arenga pinnata highlight sustainable alternatives. Integrating native forage plants into apiary landscapes is therefore recommended to support apiculture while conserving biodiversity in tropical forest ecosystems.